PENGAWASAN SATUAN POLISI PAMONG PRAJA TERHADAP PENYELENGGARAAN REKLAME BERDASARKAN PERATURAN DAERAH KOTA DUMAI NOMOR 2 TAHUN 2021 TENTANG PENYELENGGARAAN REKLAME - Silvi Isnendina; Emilda Firdaus; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research is related to the implementation of supervision of the implementation ofbillboards which is regulated in Article 35 Paragraph 1 of the Dumai City RegionalRegulation Number 2 of 2021 concerning the Implementation of Billboards which are carriedout routinely. In the field there are still many illegal billboards that are posted not inaccordance with the established provisions. Therefore, it is necessary to study the firststimulant, the supervision of the Civil Service Police Unit over the implementation ofbillboards based on the Regional Regulation of the City of Dumai Number 2 of 2021concerning the Implementation of Billboards, Second, the obstacles for the Civil ServicePolice Unit in carrying out supervision of the implementation of billboards in the City ofDumai.This research is a sociological research, because it is based on field research, namelyby collecting data from observations, interviews, and literature studies that have somethingto do with the problems studied assisted by primary, secondary and tertiary data. This studyuses qualitative data analysis, produces descriptive data, and concludes with a deductivethinking method.From the results of the study, it was concluded that, First, the arrangement forholding billboards based on the Dumai City Regional Regulation Number 2 of 2021 has notbeen maximized, Second, the supervision of the Civil Service Police Unit on theimplementation of billboards based on the Kita Dumai Regional Regulation Number 2 of2021 concerning the implementation of billboards has not run optimally. Third, the inhibitingfactors for the Civil Service Police Unit in carrying out supervision of the implementation ofbillboards in Dumai City are the lack of operational staff, the lack of coordination betweenlaw enforcers, the lack of facilities, and the lack of regulations. As for the supporting factorsfor the Civil Service Police Unit in carrying out supervision of the implementation ofbillboards, it is supported by the existence of regulations governing the implementation ofbillboards, good coordination with Satpol PP responses and supported by motivation andcommitment from Satpol PP leaders.Keywords : Arrangement-Supervision of Civil Service Police Unit-Reklame